Functional strategies of tropical dry forest plants in relation to growth form and isotopic composition. (1st November 2017) - Santiago, L S; Silvera, K; Andrade, J L; Dawson, T E
Abstract: Tropical dry forests (TDFs) undergo a substantial dry season in which plant species must endure several months of drought. Although TDFs support a diverse array of plant growth forms, it is not clear how they vary in mechanisms for coping with seasonal drought. We measured organic tissue stable isotopic composition of carbon (δ 13 C) and nitrogen (δ 15 N) across six plant growth forms including epiphytes, terrestrial succulents, trees, shrubs, herbs, and vines, and oxygen (δ 18 O) of four growth forms, to distinguish among patterns of resource acquisition and evaluate mechanisms for surviving annual drought in a lowland tropical dry forest in Yucatan, Mexico. Terrestrial succulent and epiphyte δ 13 C was around –14‰, indicating photosynthesis through the Crassulacean acid metabolism pathway, and along with one C4 herb were distinct from mean values of all other growth forms, which were between –26 and –29‰ indicating C3 photosynthesis. Mean tissue δ 15 N across epiphytes was –4.95‰ and was significantly lower than all other growth forms, which had values around +3‰. Tissue N concentration varied significantly among growth forms with epiphytes and terrestrial succulents having significantly lower values of about 1% compared to trees, shrubs, herbs and vines, which were around 3%. Tissue C concentration was highest in trees, shrubs and vines, intermediate in herbs and epiphytes and lowest in terrestrial succulents. δ 18 O did not vary among growth forms. Overall, our results suggest several water-saving aspects of resource acquisition, including the absolute occurrence of CAM photosynthesis in terrestrial succulents and epiphytes, high concentrations of leaf N in some species, which may facilitate CO2 drawdown by photosynthetic enzymes for a given stomatal conductance, and potentially diverse N sources ranging from atmospheric N in epiphytes with extremely depleted δ 15 N values, and a large range of δ 15 N values among trees, many of which are legumes and dry season deciduous.